2017
DOI: 10.1002/chem.201700045
|View full text |Cite
|
Sign up to set email alerts
|

Indications of 5′ to 3′ Interbase Electron Transfer as the First Step of Pyrimidine Dimer Formation Probed by a Dinucleotide Analog

Abstract: Pyrimidine dimers are the most common DNA lesions generated under UV radiation. To reveal the molecular mechanisms behind their formation, it is of significance to reveal the roles of each pyrimidine residue. We thus replaced the 5'-pyrimidine residue with a photochemically inert xylene moiety (X). The electron-rich X can be readily oxidized but not reduced defining the direction of interbase electron transfer (ET). Irradiation of the XpT dinucleotide under 254 nm UV light generates two major photoproducts: a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…Electronic factors : A first fundamental, though probably trivial, electronic effect to be taken into account when discussing 64‐PP formation is that oxetane formation occurs on the PES of an excited state different from that yielding CPD. Furthermore, only the CT 53 state (and not CT 35 ) is leading to dimer formation, as confirmed by recent studies on dinucleotide analogues …”
Section: Discussionsupporting
confidence: 70%
“…Electronic factors : A first fundamental, though probably trivial, electronic effect to be taken into account when discussing 64‐PP formation is that oxetane formation occurs on the PES of an excited state different from that yielding CPD. Furthermore, only the CT 53 state (and not CT 35 ) is leading to dimer formation, as confirmed by recent studies on dinucleotide analogues …”
Section: Discussionsupporting
confidence: 70%
“…33 Using an SP-containing oligonucleotide, we solved the first structure of the dinucleotide SP in duplex DNA, and found that SP induces only a minor disturbance of the DNA helical structure. 34 Additionally, using thymine isosteres, we recently extended our studies to the under-standing of the CPD 35,36 and 6-4PP photochemistry, 37 and have gained interesting mechanistic insights into the formation of these two dimers.…”
Section: LImentioning
confidence: 97%
“…Interestingly, UV irradiation of the resulting dinucleotide XpT also generates two major products, both of which exhibit an UV absorption at about 320 nm, indicating that they both contain a pyrimidone ring found in the natural 6-4PP. 37 No CPD or true SP analog (with a methylene bridge between C5 of X and C5 of T) was found. Product 1 is identified as a 6-4PP analog (Scheme 7).…”
Section: Using a Thymine Isostere To Understand 6-4pp Photoreactionmentioning
confidence: 99%
“…Stacking and pairing of nucleobases in DNA duplexes favours population of CT states that correspond to intra-strand or inter-strand electron transfer between nucleobases thus resulting in the transient formation of a radical pair. The CT states have been identied as gateways to oxidative damage and photodamage (Banyasz et al, DOI: 10.1039/c7fd00179g; Giussani et al, DOI: 10.1039/c7fd00202e; Jian et al 4 ), but at the same time they mediate energy dissipation increasing DNA photostability (Martinez-Fernandez and Improta, DOI: 10.1039/c7fd00195a). The processes are typically characterized by timeresolved spectroscopic approaches 2,3,5-9 or computation (reviewed in ref.…”
Section: Photoinduced Dna Damage and Repair By Photoreactivationmentioning
confidence: 99%